PENGARUH MOTIVASI, KOMPENSASI DAN KOMITMEN ORGANISASIONAL, TERHADAP ORGANIZATIONALCITIZENSHIP BEHAVIOR - WILLIAM GUNAWAN; NURWANTI NURWANTI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2017)
The purpose of this study is to examine the influence and the nature of the relationship between organizational citizenship behavior with three influences namely motivation, compensation, and organizational commitment. The method used in this research is descriptive and causality of respondents involved in this research as many as 41 permanent employees. This research uses purposive sample. Data collection was done by distributing questionnaires and the method for data analysis in this research is multiple linear regression. The result of this study is that there is no significant negative impact on motivation and, there is significant impact positive on compensation, organizational commitment to organizational citizenship behavior.